Democracy and leadership: the gendered voice in politics - Hazarika, Sujata D. (2008)
In Assam be it in the Maomaria revolt, nationalist movement, or a more recent constitutional mandate for political participation, women have seldom transcended institutionalised patriarchy. Most often, voices of change come from agencies of male politics where the politics behind conventional definition of the `political' is never questioned. A fuller grasp of women as political subjects or agents must, therefore, draw on a more complex conceptualisation of the field of power than is routinely encountered today. In this article an attempt is made to evaluate the political empowerment of women in Assam after the implementation of the 73rd Amendment, which facilitates the representation of women in politics. - Reproduced.
Keywords: Leadership; Women in politics